Aging and the gastrointestinal tract - Pilotto, Alberto; Malfertheiner, Peter; Holt, Peter R (Karger, 2003)
With the dramatic increase of the aging population, the study and care of gastrointestinal disorders in the elderly have become priority topics for both clinicians and researchers. The geriatric approach which includes the epidemiology and pharmacokinetics of drugs as well as a comprehensive multidimensional assessment is particularly important in managing older patients with gastrointestinal disorders, since these patients are likely to have multiple interacting problems that interfere with their daily function and complicate their treatment. This book presents the results of recent studies in geriatric gastroenterology and reviews both basic and clinical aspects of the field. An important section is devoted to the close examination of the structural and functional effects of aging on the physiology of the gastrointestinal tract.
Interdisciplinary topics in gerontology, ISSN 0074-1132 vol. 32
Keywords: gastrointestinální nemoci; geriatrie; Digestion; senioři; trávení; gastroenterologie; Aged; Gastrointestinal Diseases; Gastroenterology; GASTROINTESTINÁLNÍ SYSTÉM